Research appointment award - Angastiniotis, Nicos (My University, 2026)
Research appointment award on "Synthesis, Characterization and Properties of Nanostructured Co/WC" granted by the Laboratory for Nanostructured Materials Research at Rutgers University in collaboration with Nanodyne Inc., New Brunswick, NJ, USA and the United States Office of Naval Research (ONR) Control #N00014-91-J-1818
Keywords: Natural sciences